SUPPLEMENTARY NOTE ON THE BLACK SNOEK, THYRSITOIDES MARLEYI FOWLER,1929 (PISCES: GEMPYLIDAE) FROM INDIAN WATERS - S.SURYA,; N.S. JEENA,; N.K. MIDHUNRAJ,; P.G.AMBARISH,; K. K. SURESH,; M.K.ANIL,; B . SANTHOSH,; E.M. ABDUSAMAD,; R. PRATHIBHA, (The Bioscan, 2021)
A rare landed fish of the family Gempylidae were collected (n=19), (8º22’38.43"N, 76º59’31.67" E) and the morphometric, meristic and molecular details were analysed from Indian waters. The DNA barcode (Ac-cession no.: MG886840), upon comparison with NCBI database, confirmed that the species was Thyrsitoides marleyi, which exhibited an identity of 99% to T.marleyi from Japanese waters (Accession: AP012505.1). Fin formula is D XVIII 17, A II 16, P I 14, V I 5, C 15. Among the morphometric characters in the percentage of standard length, all characters were genetically controlled (<10%) and showed a high value of correlation coefficient (r>0.96) indicates that most of the characters exhibited a direct proportional growth to each other. One of the specimens was deposited at the National Biodiversity Museum, (Details: EB 3162205, 887.0 mm, standard length (SL)), a designated national repository of CMFRI, Kochi.